OPTIMALISASI MANAJEMEN WAKTU MAHASISWA DALAM PERSPEKTIF TAFSIR TARBAWI - Rosidin (STAI Ma'had Aly Al-Hikam Malang, 2024)
Kegagalan mahasiswa dalam mengelola waktu mengakibatkan beragam dampak negatif, seperti prokrastinasi akademik, burnout syndrome, serta minimnya study-life balance dan prestasi belajar. Artikel ini disusun menggunakan pendekatan kualitatif, jenis penelitian pustaka dan analisis tafsir tarbawi yang berintikan pada analisis lughawi (bahasa), tahlili (tafsir) dan tarbawi (kependidikan). Ada empat temuan artikel yang didasarkan pada empat dampak negatif problem manajemen waktu di kalangan mahasiswa. Pertama, prokrastinasi akademik bisa disebabkan oleh rasa malas (kasl) dan lalai (sahw). Formulasi solusi untuk meminimalisasi prokrastinasi akademik adalah aktualisasi nilai-nilai dalam ayat-ayat yang memuat terma waqt dan ajal, yang meliputi: Penjadwalan, Penyegeraan, Fleksibilitas dan Dedikasi. Kedua, burnout syndrome bisa disebabkan oleh kelelahan fisik (nashb) dan psikis (dhiq). Formulasi solusi untuk meminimalisasi burnout syndrome adalah aktualisasi nilai-nilai dalam ayat-ayat yang memuat terma yaum, syahr dan sanah, yang meliputi: Variasi kegiatan harian, Produktif di masa perkuliahan dan healing di masa liburan dan Motivasi lulus kuliah tepat waktu. Ketiga, study-life balance mahasiswa dipengaruhi oleh mindset adil (‘adl) dan moderat (tawassuth). Formulasi solusi untuk optimalisasi study-life balance mahasiswa adalah aktualisasi nilai-nilai dalam ayat-ayat yang memuat terma nahar dan lail, yang meliputi: Keseimbangan aktivitas siang dan malam, Keseimbangan aktivitas dan istirahat serta Keseimbangan perkuliahan dan ibadah. Keempat, prestasi belajar mahasiswa dipengaruhi oleh mentalitas juara (sabq) dan sukses (falah). Formulasi solusi untuk optimalisasi prestasi belajar mahasiswa adalah aktualisasi nilai-nilai dalam ayat-ayat yang memuat terma ‘ashr dan ghudwah-ghadah, yang meliputi: Fungsionalisasi waktu, Pembiasaan bangun pagi dan Disiplin evaluasi diri. University students’ failure to manage their time results in various negative impacts, such as academic procrastination, burnout syndrome, and lack of study-life balance and learning achievement. This article was prepared using a qualitative approach, a type of library research and analysis of Qur’anic educational interpretation (tafsir tarbawi) which has as its core an analysis of lughawi (language), tahlili (interpretation) and tarbawi (education). There are four article findings based on four negative impacts of time management problems among university students. First, academic procrastination can be caused by a laziness (kasl) which results in negligent attitude (sahw). The formulation of a solution to minimize academic procrastination is the actualization of values ​​in verses containing the terms waqt and ajal, which include: Time scheduling, Act immediately, Flexibility and Dedication. Second, burnout syndrome can be caused by physical (nasb) and psychological (diq) fatigue. The formulation of a solution to minimize burnout syndrome is the actualization of values ​​in verses containing the terms yaum, shahr and sanah, which include: Variation of daily activities, Productivity during study time and healing during holidays, and Motivation to graduate from university on time. Third, students’ study-life balance is influenced by a fair ('adl) and moderate (tawassut) mindset. The formulation of a solution for optimizing students' study-life balance is the actualization of the values ​​in the verses which contain the terms nahr and lail, which include: Balance of day and night activities, Balance of activities and rest, and Balance of study and worship. Fourth, student learning achievement is influenced by the mentality of winning (sabq) and success (falah). The formulation of a solution for optimizing student learning achievement is the actualization of values ​​in verses that contain the terms 'ash and ghudwah-ghadah, which include: Functionalization of time, the Habit of getting up early and the Discipline of self-evaluation.